Peran Media Sosial Instagram @rumahvaksinasi_garut dalam Meningkatkan Akses dan Kesadaran Vaksinasi - Hisam Sambadi; Iis Zilfah Adnan; Sani Rahman (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine the role of the Instagram account @rumahvaksinasi_garut in enhancing access to and awareness of vaccination in Garut Regency. Using a qualitative descriptive method and Pierre Levy’s New Media theory as the foundation, this research explores how Instagram functions as an interactive and network-based digital communication medium. Data were collected through interviews, observations, and documentation of Instagram content. Thematic analysis was applied to understand how educational content, vaccination schedules, testimonials, and interactive features such as Q&A and polls create an active and responsive communication space. The findings indicate that Instagram @rumahvaksinasi_garut effectively provides easily accessible vaccination information and fosters an active social interaction space between administrators and the community. Through educational content, testimonials, and interactive features, this account successfully builds trust and community participation in vaccination programs. Consistent and strategic use of social media makes Instagram an effective communication tool to expand vaccination coverage and raise public health awareness in the rapidly evolving digital era.